Lamin Dayak Kenyah Architecture as a Medium for English Language Instruction: A Cultural Approach - Fitriani, Yustina; Bandung, Murti (LPPM Universitas Bumigora Mataram, 2025)
This study explores the integration of Lamin Dayak Kenyah architecture as a cultural medium in English language instruction. The research aims to promote contextual and culture-based learning by linking English teaching materials with local wisdom embedded in the traditional Lamin house. A qualitative descriptive method was employed in this study, involving 30 university students and five English lecturers from East Kalimantan. Data were collected through observations, interviews, and document analysis conducted with local cultural experts and English educators. The data were analyzed thematically using NVivo software. The findings reveal that Lamin architecture, rich with symbolic meanings, social values, and traditional narratives, provides authentic contexts for developing students’ linguistic and intercultural competence. Incorporating cultural artifacts such as Lamin into English instruction not only enhances students’ engagement and comprehension but also fosters awareness of cultural identity and appreciation for indigenous heritage.